Emotional Literacy of Elementary School Teachers: A Study on Science Learning with Problem-Based Learning (PBL) and Homogeinity Psycho Cognition (HPC) Program - Leasa, Marleny; Pelamonia, Johanes; Talakua, Melvie; Batlolona, Rafafy (KnE Social Sciences, 2024)
In the 21st century era, students learn not only to live now but also to live in the future, which is full of dynamics and the surge of globalization. Schools should strive to create a social-emotional environment that supports the development of students' emotional aspects, including by implementing relevant social-emotional learning. Emotional literacy with problem-based learning (PBL) and homogeneity psycho cognition (HPC) learning programs is an unexplored research field in Indonesia, especially in biological science learning in elementary schools and even at higher levels. This research was conducted to explore PBL programs and emotional literacy in depth. This research aims to examine the influence of the PBL learning model with HPC strategies on the emotional literacy of elementary school students in Ambon City. This research is quasi-experimental research, where emotional literacy is the dependent variable and the PBL learning model while HPC strategies is the independent variable. The research results show that there is no difference in emotional literacy between the treatment groups. This means that the implementation of the 2013 curriculum and the Merdeka curriculum in elementary schools have made positive contribution to the learning and emotional environment of elementary school students. Thus, any learning model no longer affects students' emotional literacy. Keywords: emotional literacy, PBL with HPC strategy, emotional environment, elementary schools